Characterization of latently infected EBV+ antibody-secreting B cells isolated from ovarian tumors and malignant ascites - Zhang, Lixin; Strange, Mary; Elishaev, Esther; Zaidi, Syed; Modugno, Francesmary; Radolec, Mackenzy; Edwards, Robert P.; Finn, Olivera J.; Vlad, Anda M. (Frontiers in Immunology, 2024)
Intra-tumoral B cells mediate a plethora of immune effector mechanisms with key roles in antitumor immunity and serve as positive prognostic indicators in a variety of solid tumor types.Using tumor tissue or ascites from four different patients with epithelial ovarian cancer, we report that Epstein Barr virus (EBV)-positive, antibody-secreting B lymphocytes can be isolated from the tumor microenvironment. In each case, the originating tumor tissue showed presence of B and T lymphoid aggregates. Upon in vitro culture, the cells showed presence of EBV proteins and underwent spontaneous immortalization in an antibody-secreting state. Immune profiling of the cell lines shows the presence of plasma cell markers and an antigen-experienced, memory phenotype, and BCR sequencing reveals high clonality. Using a human proteome array comprising more than 21,000 proteins for target identification, followed by ELISA for validation, we demonstrate that the antigens recognized by three of the four cell lines are coilcoil domain containing protein 155 (CCDC155), growth factor receptor-bound protein 2 (GRB2), and pyruvate dehydrogenase phosphatase2 (PDP2), respectively. These studies offer a new perspective on EBV latency in tumor-infiltrating memory B cells and identification of their secreted antibodies in non-EBV-related diseases, such as ovarian cancer.